2008
DOI: 10.17221/407-pse
|View full text |Cite
|
Sign up to set email alerts
|

Growth, water status and nutrient accumulation of seedlings of Holoptelea integrifolia (Roxb.) Planch in response to soil salinity

Abstract: Greenhouse experiments were conducted to assess the effects of soil salinity on emergence, growth, water status, proline content and mineral accumulation of seedlings of Holoptelea integrifolia (Roxb.) Planch (Ulmaceae). NaCl was added to the soil and salinity was maintained at 0.3, 3.9, 6.0, 7.9, 10.0, 12.1 and 13.9 dS/m. Salinity caused reduction in water potential of tissues, which resulted in internal water deficit to plants. Consequently, seedling growth significantly decreased with increase in soil salin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
14
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 15 publications
3
14
0
1
Order By: Relevance
“…Cl -is the most prevalent anion under saline conditions. To prevent these problems, plants suppress the influx and accumulation of Na + in the cytoplasm, especially in leaves (Esmaili et al 2008, Patel andPandey 2008). We found that, in all tissues under salt stress, the Na + and Cl -contents increased dramatically in salt-sensitive cultivars.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…Cl -is the most prevalent anion under saline conditions. To prevent these problems, plants suppress the influx and accumulation of Na + in the cytoplasm, especially in leaves (Esmaili et al 2008, Patel andPandey 2008). We found that, in all tissues under salt stress, the Na + and Cl -contents increased dramatically in salt-sensitive cultivars.…”
Section: Discussionsupporting
confidence: 47%
“…Plants subjected to such environments, take up high amounts of Na + (Esmaili 2008), whereas the uptake of K + and Ca 2+ is considerably reduced (Patel and Pandey 2008). Reasonable amounts of both K + and Ca 2+ are required to maintain the integrity and functioning of cell membranes (Ashraf 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main negative effects of high salinity that influence plant growth and development are photosynthesis inhibition (Sharma et al 2005), water deficit (Suárez and Medina 2008), ion toxicity associated with excessive Cl -and Na + (Afzal et al 2008, Patel andPandey 2008), interference with nutrition leading to nutrient imbalance (Misra et al 1997). Bastías et al (2004) have reported that high concentrations of salt disrupt homeostasis in water relations and change the ion distribution at both cellular and whole plant levels.…”
mentioning
confidence: 99%
“…Hence, better understanding of the mechanisms that enable plants to adapt to salt stress is necessary for exploiting saline soil (Patel and Pandey 2008). Silver buffaloberry (Shepherdia argentea (Pursh) Nutt.)…”
mentioning
confidence: 99%